2017
DOI: 10.1108/f-06-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

A review on indoor environmental quality (IEQ) and energy consumption in building based on occupant behavior

Abstract: The purpose of this paper is to reviews the concept of occupant behavior and its relation with IEQ and building energy consumption. The behavior is referred to any direct or indirect action, which is selected by occupant to manage the unpleasant indoor environmental conditions. Thermal comfort, indoor air quality, aural comfort and visual comfort, are the key factors of IEQ evaluation. Human behavior interacts with energy consumption in buildings significantly. Design/methodology/approach-Each IEQ parameters r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 39 publications
0
48
0
1
Order By: Relevance
“…The only significant difference (P < .01) was found for isobutane between the apartments (46 μg/m 3 ) and the other houses (5.5 μg/m 3 ). Nonetheless, the results should be interpreted with caution given the small number of sampled apartments (8).…”
Section: Influence Of Dwelling Characteristics On Voc Concentrationsmentioning
confidence: 89%
“…The only significant difference (P < .01) was found for isobutane between the apartments (46 μg/m 3 ) and the other houses (5.5 μg/m 3 ). Nonetheless, the results should be interpreted with caution given the small number of sampled apartments (8).…”
Section: Influence Of Dwelling Characteristics On Voc Concentrationsmentioning
confidence: 89%
“…Most researchers believe the certified GBs perform better than conventional buildings in terms of IEQ and energy use [148][149][150]. There are four main variables highlighted in GBRSs to improve IEQ: thermal quality, acoustic quality, visual quality, and indoor air quality (IAQ) [151][152][153]. Lin et al found the satisfaction of users in certified GBs is higher than conventional buildings in terms of thermal comfort and IAQ [154].…”
Section: Technologies Applicationmentioning
confidence: 99%
“…Buildings are designed and constructed generally for human habitation, as a result, the requirements for their usage is needed to be fulfilled as a precondition for their well-being [3]. Different studies on IEQ in buildings have shown that, achieving comfort in an indoor environment should be based on the assessment of thermal, acoustic, lighting and the quality of the indoor air as parameters of importance [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been asserted that the assessments of the overall indoor environmental quality of office buildings do not follow any standard protocol [8]. This is also typical of hospital facilities where little has been done in assessing their indoor environmental quality, which has great impact on occupants' health, productivity as well as building energy demand [6,9]. There is a need therefore, to have a standard measure for the overall indoor environmental quality of hospital buildings in order to prevent the negative impact of the environment on building occupants.…”
Section: Introductionmentioning
confidence: 99%